THE FREEDOM OF EXPRESSION IN MASS MEDIA, AUDIOVISUAL AND THE ONLINE ENVIRONMENT - Stepanov, Georgeta; Ristea, Georgiana Alina (My University, 2021)
Mass-media represents the main tool of a democratic society and it refers to two fundamental rights: the right to be informed and the freedom of expression. Beyond its functions, however, mass-media represents a product of the society which is formed and functions. In this framework characterised by freedom and participation, mass-media holds a consolidation role for the new society, it supports and monitors a true democracy, it takes part in a correct government and it leads to economic development. As “the fourth power in the state”, the press creates the new public opinion and the new civil society. The risks of fulfilling its duty and the audacity of applying its freedom of expression presented, at times, irreparable consequences. At the same time, the freedom of expression, both of the media and of the individual, represents a fundamental right. The freedom of expression can neither prejudice the dignity, honour, or the particular life of a individual, or the right to self-image. Exerting the right to free expression involves certain duties and responsibilities.
Keywords: civil society; democracy; lack of censorship; selfimage; freedom of expression